Equinoideos de mar profundo (Echinodermata: Echinoidea) del Pacífico mexicano - Conejeros-Vargas, Carlos Andrés; Solís-Marín, Francisco Alonso; Laguarda-Figueras, Alfredo (Revista de Biología Tropical, 2017)
Deep-sea echinoderms (Echinodermata: Echinoidea) from the Mexican Pacific. The coastal strip of the Mexican Pacific and Gulf of California includes 11 states, and considering Isla Guadalupe and the Revillagigedo archipelago, Mexico has 2 364 200 km2 of marine extension in the Pacific Ocean. Studies of deep benthic macroinvertebrates for this area began with the Albatross, which traveled from the Guadalupe Islands to Guaymas in 1891. To date, 26 species of echinoids have been reported, with a bathymetric range that exceeds 200 m. In the present work, the previous bibliographic records for echinoids that were collected within the limits of the Mexican Pacific were corroborated. The taxonomic identity of the 26 species reported was also corroborated by 11 689 specimens deposited in four scientific collections: two Mexican collections (3 322 specimens in the National Collection of Echinoderms “Dra. M. E. Caso” of the ICML, UNAM and 6 673 specimens deposited in the Invertebrate Reference Collection of the Mazatlán Station - ICML, UNAM) and two international collections (1 420 specimens deposited at the National Museum of Natural History, Smithsonian Institution, Washington, DC, and 140 specimens deposited at the Museum of Comparative Zoology, Harvard University). No collection records were found at depths greater than 200 m for the species Lytechinus pictus (Verrill, 1867), Clypeaster europacificus H.L. Clark, 1914, Dendraster excentricus (Eschscholtz, 1831), Lovenia cordiformis A. Agassiz, 1872 and Brissus obesus Verrill, 1867. No records were found for Kamptosoma asterias (A. Agassiz, 1881), Araeolampas fulva (A. Agassiz, 1879) and Nacospatangus depressus H.L. Clark, 1917, which belonged to specimens collected within the limits of the Mexican Pacific. Within the material examined in the scientific collections specimen records were found only for 18 of the 26 species of sea urchins that were collected at a depths greater than 200 m in the Mexican Pacific. No bibliographic record or specimens were found to validate geographic or bathymetric distribution for eight species. Rev. Biol. Trop. 65(Suppl. 1): S244-S252. Epub 2017 November 01.